2012
DOI: 10.1176/appi.ajp.2012.11091337
|View full text |Cite
|
Sign up to set email alerts
|

Combined Cognitive Remediation and Functional Skills Training for Schizophrenia: Effects on Cognition, Functional Competence, and Real-World Behavior

Abstract: In a short intervention, cognitive remediation produced robust improvements in neurocognition. Generalization to functional competence and real-world behavior was more likely when supplemental skills training and cognitive remediation were combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
176
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(201 citation statements)
references
References 38 publications
10
176
0
13
Order By: Relevance
“…Some evidence suggests that FC may be more proximal to functional deficits that NP performance, suggesting that the influence of cognitive deficits on disability may be mediated through influences on the ability to perform functional skills. In addition, in a recent study, we demonstrated that FC and NP performance responded to different interventions, suggesting that despite their correlation in naturalistic studies, these may be subtly different domains of functioning requiring separate interventions in order to improve functioning [8]. We will return to this issue later for a specific discussion of the interaction between cognitive limitations and the specific skills that are required to succeed in health management activities, including food preparation and planning.…”
Section: Introductionmentioning
confidence: 89%
“…Some evidence suggests that FC may be more proximal to functional deficits that NP performance, suggesting that the influence of cognitive deficits on disability may be mediated through influences on the ability to perform functional skills. In addition, in a recent study, we demonstrated that FC and NP performance responded to different interventions, suggesting that despite their correlation in naturalistic studies, these may be subtly different domains of functioning requiring separate interventions in order to improve functioning [8]. We will return to this issue later for a specific discussion of the interaction between cognitive limitations and the specific skills that are required to succeed in health management activities, including food preparation and planning.…”
Section: Introductionmentioning
confidence: 89%
“…Ten of the sixteen studies found supportive evidence of generalizability to functional outcomes [12][13][14][15][16][17][18][19][20][21]. One study [22] reported no improvement in functional outcome and another study [12] found that functional outcomes improved when skills-training followed CR, but not after CR alone. Although it is not a focus of this review, a few studies observed improvements in clinical symptoms after CR and posit that neurocognitive impairment is closely associated with negative symptoms [23].…”
Section: Higher-level Cr Approachesmentioning
confidence: 91%
“…[59][60][61][62][63][64][65][66][67][68] While the first report meeting these criteria was published in 2006, most of the remaining articles were published in the last 3 years, probably after the aforementioned recommendations were implemented by the FDA. Five of these trials were designed to evaluate the effects of drug therapy with atypical antipsychotics (risperidone, quetiapine, lurasidone), a neuropeptide (davunetide), or other potential cognitionenhancing drugs.…”
Section: The Use Of Functional Capacity Measures In Clinical Trialsmentioning
confidence: 99%